Die Substantiierungslast im Zivilprozess - Rust, Max (Schriften zum Prozess- und Verfahrensrecht, 2021)
The importance of Substantiierungslast (pleading requirements) for the practice of German civil procedure law can hardly be overstated: For a lawyer, the success of the lawsuit is at stake; for a judge, the Substantiierungslast provides procedural grounds to dismiss a case without taking evidence. In this context, fishing expeditions, general and specific denial as well as denial based on lack of sufficient knowledge are discussed. The author points out concerning developments, such as violations of the right to a fair hearing due to an over-reliance on pleading requirements, limited ways to appeal such decisions, and the Federal High Court's increasing willingness to instrumentalize procedural burdens.